Social innovation and entrepreneurial education in the context of and reflections on a European Research Project in the third sector - Ayub, Asad; Eurich, Johannes (Diaconia, 2022)
This paper explores the impact of social innovation education on professionals working in diaconia and the wider social economy within various welfare-state contexts. Welfare states have demonstrated an increasing interest in the development of social innovation. There is a wide variety of models of welfare states in Europe, and different countries are at various stages of incorporating the concept of social innovation into their social-service provisions. Nevertheless, our social innovation education program participants shared many common challenges and learnings. This paper focuses not only on the theoretical framework around the concepts of social innovation in the context of the welfare states, it also shares valuable insights that emerged because of implementing a social innovation education program for 2 years (2021-2022) and argues for the relevance of social innovation education for leaders of diaconal organizations.